'I've got to get something out of it. And so do they': experiences of people with aphasia and university students participating in a communication partner training programme for healthcare professionals. Issue 5 (5th June 2018) - Cameron, Ashley; Hudson, Kyla; Finch, Emma; Fleming, Jennifer; Lethlean, Jennifer; McPhail, Steven
Abstract: Background: Communication partner training (CPT) has been used to support communication partners to interact successfully with people with aphasia (PWA). Through successful CPT interaction PWA's accessibility to healthcare is notably improved. The present study sought to build on prior studies by investigating the experiences of individuals with aphasia and healthcare providers to ascertain what they deemed to be beneficial from CPT and what could be refined or improved, dependent on the setting and skill set of those participating. Aims: To gain an understanding of the experiences of PWA involved in the provision of CPT to health professional (HP) students. Also to investigate the experiences of HP students who participated in the CPT programme. Methods & Procedures: Eight PWA and 77 HP students who had completed a CPT programme participated in a focus group/semi‐structured interview (PWA) and feedback session (HP students) moderated by two speech–language pathologists (SLPs). These sessions were recorded (audio and video), transcribed verbatim, including non‐verbal communication, and analyzed using qualitative content analysis. Outcomes & Results: Overall, the study sought to understand experiences of the training. Both the PWA and HP students reported positive experiences of CPT. PWA discussed their perception that CPT improved HPs and HP students' understanding and interactions conversing with them and emphasized the need for training and education for all health related professions. HP students enjoyed the opportunity to experience interacting with PWA, without being 'assessed' and felt it consolidated their learning based on lecture content. Conclusions & Implications: Inclusive and accessible healthcare is paramount to ensure the engagement of patients and providers. Based on the experiences and feedback of the participants in this current study, CPT offers a salient and practical training method with potential to improve practice. Participants perceived CPT to be beneficial and validated the need for the training to support PWA accessing healthcare.